2023
DOI: 10.1186/s12864-023-09579-9
|View full text |Cite
|
Sign up to set email alerts
|

Complete-genome sequencing and comparative genomic characterization of blaNDM-5 carrying Citrobacter freundii isolates from a patient with multiple infections

Jianzhong Ye,
Lulu Jin,
Yaling Li
et al.

Abstract: Background The emergence and wide spread of carbapenemase-producing Enterobacteriaceae (CPE) poses a growing threat to global public health. However, clinically derived carbapenemase-producing Citrobacter causing multiple infections has rarely been investigated. Here we first report the isolation and comparative genomics of two blaNDM-5 carrying Citrobacter freundii (C. freundii) isolates from a patient with bloodstream and urinary tract infections. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Interestingly, these isolates all belonged to the ST22 C. freundii strain and were distributed in different countries over the span of a decade, which suggested that the ST22 C. freundii strains have disseminated globally and they may be highly clonal. Notably, C. freundii BC73 co-carrying bla NDM-1 and bla IMP-4 and C. freundii DY2007 harboring bla NDM-5 , isolated from dongyang, China in 2020 ( Ye et al, 2023 ), were found to be the most closely related isolates. Previous report has described that the differences between bla NDM-1 and bla NDM-5 were represented by mutations at only two specific sites (88, 154) ( Sun et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, these isolates all belonged to the ST22 C. freundii strain and were distributed in different countries over the span of a decade, which suggested that the ST22 C. freundii strains have disseminated globally and they may be highly clonal. Notably, C. freundii BC73 co-carrying bla NDM-1 and bla IMP-4 and C. freundii DY2007 harboring bla NDM-5 , isolated from dongyang, China in 2020 ( Ye et al, 2023 ), were found to be the most closely related isolates. Previous report has described that the differences between bla NDM-1 and bla NDM-5 were represented by mutations at only two specific sites (88, 154) ( Sun et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was isolated from the urine of a 64-year-old patient with urinary tract infections resulting from total cystotomy and abdominal fistula drainage. Carbapenems resistant Citrobacter freundii isolates, especially multidrug-resistant strains, were gradually being found in urinary tract infections, which may cause the extension of infection and the increase of patients’ suffering ( Prussing et al, 2020 ; Zhang et al, 2021 ; Ye et al, 2023 ). The AST results presented in Table 1 showed that C. freundii BC73 and transconjugant BC73-J53 were resistance to all β-lactams, chloramphenicol, minocycline, azithromycin, and gentamicin antibiotics tested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation